2017
DOI: 10.2147/dddt.s105207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of alpha-1 proteinase inhibitor in the management of adult patients with severe alpha-1 antitrypsin deficiency: a review of the current literature

Abstract: Alpha-1 antitrypsin (AAT) functions primarily to inhibit neutrophil elastase, and its deficiency predisposes individuals to the development of chronic obstructive pulmonary disease (COPD). The putative protective serum concentration is generally considered to be above a threshold of 11 μM/L, and therapeutic augmentation of AAT above this value is believed to retard the progression of emphysema. Several AAT preparations, all derived from human donor plasma, have been commercialized since approval by the US Food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Neutrophil elastase is one of the main targets of α1-antitrypsin, an acute-phase reactant protein that functions primarily as a serine protease inhibitor. 229 The recent R andomized, placebo-controlled trial of augmentation therapy in A lpha 1- P roteinase I nhibitor D eficiency (RAPID) and the RAPID Extension trials confirmed the benefits of α1-antitrypsin therapy in slowing disease progression in patients with α1-antitrypsin deficiency. 230…”
Section: Intracellular Location and Multiple Cellular Sources Of Chymmentioning
confidence: 98%
“…Neutrophil elastase is one of the main targets of α1-antitrypsin, an acute-phase reactant protein that functions primarily as a serine protease inhibitor. 229 The recent R andomized, placebo-controlled trial of augmentation therapy in A lpha 1- P roteinase I nhibitor D eficiency (RAPID) and the RAPID Extension trials confirmed the benefits of α1-antitrypsin therapy in slowing disease progression in patients with α1-antitrypsin deficiency. 230…”
Section: Intracellular Location and Multiple Cellular Sources Of Chymmentioning
confidence: 98%
“…[12][13][14] In this context, it would be of great help to identify responders to AT, patients that share some characteristics that either increase the concentrations or activity of proteases or make them more susceptible to the effects of proteases; however, the largest placebocontrolled, randomized clinical trial of AT to date included only 90 patients per arm, which makes subgroup analysis of responders unfeasible. 6 Some authors have proposed a personalized approach to AT considering variables such as age, rate of decline of lung function and CT imaging of the lungs; 11,14,32 our results indicate that most experts consider these variables for the prescription of AT despite the lack of definitive evidence.…”
Section: Discussionmentioning
confidence: 77%
“…As mentioned before, it is believed that A1AT augmentation can retard the progression of emphysema. Intravenous A1AT augmentation therapy has been in use for more than 20 years already and the results show that it is a safe procedure with positive consequences for treated patients [91].…”
Section: Resultsmentioning
confidence: 99%